Military culture and education - Higbee, Douglas (Ashgate, 2010)
While studies of American military culture have proliferated in recent years, and the culture of academic institutions has been a subject of perennial interest, comparatively little has been written on the ways the military and academe intersect. These essays offer both ground-level perspectives of the classroom and campus, and well-considered articulations of the tensions and opportunities involved in training civic-minded soldiers on the issues especially important in the post-9/11 world.